Consumption of Cinara spp. (Hemiptera, Aphididae) by Cycloneda sanguinea (Linnaeus, 1763) and Hippodamia convergens Guérin-Méneville, 1842 (Coleoptera, Coccinellidae) - Josiane Teresinha Cardoso; Sonia Maria Noemberg Lázzari (Revista Brasileira de Entomologia, 2003)
Adults and larvae of coccinellids were observed feeding on populations of the giant conifer aphids Cinara spp. on Pinus spp., in Southern Brazil. The objective of this research is to evaluate the consumption capacity of Cycloneda sanguinea (Linnaeus, 1763) and Hippodamia convergens Guérin-Méneville, 1842 (Coleoptera, Coccinellidae) on these aphid species, in order to obtain information for biological control programs. Ten larvae of each predator species were fed with aphids of small size (nymphs of 1st and 2nd instars), and 10 with aphids of medium size (nymphs of 3rd and 4th instars), maintained under 15ºC, 20ºC and 25ºC, 12 h photophase and 70 ± 10% relative humidity. The aphids were counted every 24 hours, replacing those that were consumed. The total consumption of Cinara by the larvae of C. sanguinea was not statistically different at the three temperatures: 325.5; 322.2 and 324.8 of small aphids and 121.3; 140.4 and 109.9 of medium ones, respectively at 15ºC, 20ºC and 25ºC. The consumption by H. convergens was higher than by C. sanguinea and increased noticeably with temperature: 444 aphids at 15ºC; 491.3 at 20ºC and 513.3 at 25ºC, considering the small aphids, and 187.1; 205.1 and 216.6 of medium aphids at the three temperatures. The small aphids weigh about half as much as medium ones and were preferred by all larval instars probably because they are easier to manipulate than the large ones. Both predators, especially the 4th instar larvae, showed high consumption capacity on the Cinara nymphs at all temperatures and can be regarded as promising biological control agents.